IMPROVING SCHOOL PRINCIPAL COMPETENCE IN IMPLEMENTING ACADEMIC SUPERVISION THROUGH MONITORING AND EVALUATION METHODS IN INDRAGIRI HULU REGENCY - Sartana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the large number of principals who do not conduct supervision and evaluation on academic supervision in schools, because they just serve as principals, resulting in low learning quality. For this reason, this study aims to improve the competency of principals in carrying out academic supervision through monitoring and evaluation. This research was an action research conducted with 10 primary school principals in Indragiri Hulu. The instrument used was an observation sheet to observe the implementation of supervision, which was used as material for analysis and follow-up improvement in the competency of the principals. The results of the study found that the implementation of academic supervision in the first cycle was 77%, which meant the competency of principals was in the enough category, while in the second cycle it increased to 88%, which was included in the good category. Based on the results of the study, it can be concluded that the competency of principals in Indragiri Hulu in implementing academic supervision has increased through monitoring and evaluation.